Insecticide Resistance and Management Strategies in Urban Ecosystems - Fang Zhu; Laura Lavine; Sally O’Neal; Mark Lavine; Carrie Foss; Douglas Walsh (Insects, 2016)
The increased urbanization of a growing global population makes imperative the development of sustainable integrated pest management (IPM) strategies for urban pest control. This emphasizes pests that are closely associated with the health and wellbeing of humans and domesticated animals. Concurrently there are regulatory requirements enforced to minimize inadvertent exposures to insecticides in the urban environment. Development of insecticide resistance management (IRM) strategies in urban ecosystems involves understanding the status and mechanisms of insecticide resistance and reducing insecticide selection pressure by combining multiple chemical and non-chemical approaches. In this review, we will focus on the commonly used insecticides and molecular and physiological mechanisms underlying insecticide resistance in six major urban insect pests: house fly, German cockroach, mosquitoes, red flour beetle, bed bugs and head louse. We will also discuss several strategies that may prove promising for future urban IPM programs.